CHARACTER ANALYSIS OF DEXTER MORGAN FROM DEXTER TV SHOW: WITH SPECIAL REFERENCE TO PSYCHOPATH OR SOCIOPATH DISORDERS - Sulistyo Dwi Antoko; Muhammad Natsir; Nita Maya Valiantien (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni dan Budaya, 2018)
ABSTRACT Dexter Morgan is the master of horrendous crimes without everyone acknowledgement, he is the master manipulator reflected through each episodes of Dexter TV Show. By using descriptive qualitative method, this study aimed to answer the following questions. The first research question is about the characters of Dexter Morgan, and the second research question is about how he conceals himself from the society. By using theories from Robert Hare’s Psychopathy Checklist –Revised (PCL- R) and Hervey M. Cleckley’sThe Mask of Sanity, the questions are answered in a direct way. The results of the study showed that Dexter Morgan matches 19 from 20 of PCL- R traits from both two factors (Personality and Behavior) such as charming personality, grandiose of self-worth, proneness to boredom, liar, manipulative, lack of remorse, shallow affect, poor and early behavioral problems, promiscuous sexual behavior, lack of realistic goals, impulsive, irresponsible, cannot accept responsibility, short-term relationship, juvenile delinquency, and criminal versatility. The only exception in the trait is from second factor which is revocation of conditional release, because Dexter Morgan never got caught, so he does not need to escape or bail from restraining orders.The result of the second research question showed how psychopath or sociopath lurking around in our peaceful society filled with happiness and joys by faking a smile and superficial charming personality. Psychopath conceals themselves in our everyday lives. Based on the answers of research questions, Dexter Morgan has dominant character as a high functioning psychopath because he can manipulate everyone, undetected serial killer, and act like a wolf in sheep clothes. Keywords: Psychopath, Sociopath, Psychological, Conceals, Dexter Morgan  ABSTRAK Dexter Morgan adalah seorang ahli dalam memanipulasi kehidupan dan juga seorang kriminal tak terdeteksi. Dengan menggunakan metode deskriptif kualitatif, penilitian ini bertujuan untuk menjawab pertanyaan sebagai berikut. Pertanyaan pertama adalah tentang karakter dari Dexter Morgan, dan yang kedua adalah tentang bagaimana Dexter Morgan menyembunyikan identitas dirinya yang sebenarnya di kehidupan sosial. Dengan menggunakan teori dari Robert Hare yang bernama Psychopathy Checklist – Revised (PCL –R) dan Harvey M.Cleckley yang berjudul The Mask of Sanity. Hasil dari penilitian ini adalah Dexter Morgan mampu membuktikan bahwa ia sangat fit dengan 19 dari 20 kriteria PCL –R dari kedua faktor (Kepribadian dan Kebiasaan) seperti kepribadian yang mempesona, kebanggaan berlebihan terhadap diri sendiri, cepat bosan, pembohong, manipulatif, kurangnya perasaan menyesal, kosong, mempunyai masalah kebiasaan sejak dini, kebiasaan seksual yang acak, kurangnya tujuan realistis, bertindak tanpa berfikir, tidak bertanggung jawab, tidak bisa menanggung tanggung jawab terhadap diri sendiri, hubungan jangka pendek, dan lain sebagainya. Satu-satunya kriteria yang tidak dipenuhi Dexter Morgan adalah pembebasan dengan syarat tertentu, karena Dexter Morgan tidak pernah tertangkap oleh pihak berwajib, ia tidak perlu di bebaskan dengan syarat. Sedangkan jawaban dari pertanyaan kedua adalah bagaimana seorang psikopat atau sosiopat menguntit dalam kehidupan sehari-hari kita menggunakan senyuman palsu dan juga keahlian untuk memanipulasi kerabat atau teman-teman di kehidupan sosial.  Berdasarkan jawaban dari kedua pertanyaan, Dexter Morgan sangat dominan dengan sifat psikopat dalam dirinya sehingga ini membuat ia adalah psikopat berkemampuan tinggi, ia hebat memanipulasi dan juga pembunuh tak terdeteksi, ia adalah serigala dalam jubah domba. Kata kunci: Psikopat, Sosiopat, Psikologi, Menyembunyikan, Dexter Morgan.